Online Learning Engagement Model for International Students in Indonesia amid Covid-19 Period: A Conceptual Model Proposal - Mussa Saidi Abubakari (International Islamic University Islamabad, 2021)
Universities in Indonesia implemented online learning following the command by the government as among the ways to mitigate the Covid-19 infections. However, fully online learning is a new experience for most educators and students including international students in Indonesia. Little is known about factors influencing online learning engagement, particularly in relation to international students. Therefore, this study proposes a conceptual model of online learning engagement based on literature review. Thus, method used is reviewing previous studies obtained from various academic journals which discussed the concept of student engagement and its related factors. The results of literature analysis indicate that student engagement is a crucial factor towards student academic and nonacademic success. Also, findings from analysis indicate that, learner engagement is influenced by a number of factors such as institutional support, instructor interactivity, student motivation, and learning material interactivity. Finally, the conceptual model of online learning engagement is proposed based on previous empirical studies. Recommendation for future studies is also discussed.